Machining behavior of AA6351–SiC–B4C hybrid composites fabricated by stir casting method. (2nd September 2016) - Kumaran, S. Thirumalai; Uthayakumar, M.; Slota, Adam; Aravindan, S.; Zajac, Jerzy
ABSTRACT: This study presents an effective approach to assess the machinability of 6351 aluminum alloy matrix, reinforced with 5 wt.% silicon carbide (SiC) and (0, 5, and 10 wt.%) boron carbide (B4 C) particles. The turning tests are carried out with a polycrystalline diamond (PCD) tool to identify the effect of the B4 C particles addition to the composite, with an objective to improve the material removal rate (MRR) and to reduce the surface roughness (Ra) and power consumption (P). The significant level of each factor, which contributes to affect the output response, is found through analysis of variance (ANOVA). The results show that the inclusion of B4 C particles in the hybrid composite significantly affects the machinability, with a contribution to the surface roughness by 7.87% and P by 6.36%. The increase in MRR affects the quality of the material, irrespective of the composites.